2015
DOI: 10.5539/jas.v7n8p205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Water Salinity on the Growth of Quinoa Plant Seedlings

Abstract: The experiment aimed to study the effect of the irrigation water quality on the growth of seedlings and its yield of quinoa plant through some traits i.e., plant height, number of leaves per plant, 1000 grains weight, dry weight per plant , stem diameter, inflorescence length and grain yield per plant. Four treatments were used as follow: T1 (low salinity water, EC 1.25 dS m -1 ), T2 (mix water between low salinity water and agricultural drainage water at ratio 1:1, EC 4 dS m -1 ), T3 (agricultural drainage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
5
11
0
3
Order By: Relevance
“…The analysis of data also indicated that all the studied yield components have had a pronounced effect on the grain yield/plant as influenced by water salinity. The same trend was obtained by Algosaibi et al (2015). This indicates that the plant can tolerate salinity of up to 3 dS.m -1 without affecting its productivity, but if the salinity exceeds that, it leads to influence on some traits of growth and production.…”
Section: Resultssupporting
confidence: 79%
“…The analysis of data also indicated that all the studied yield components have had a pronounced effect on the grain yield/plant as influenced by water salinity. The same trend was obtained by Algosaibi et al (2015). This indicates that the plant can tolerate salinity of up to 3 dS.m -1 without affecting its productivity, but if the salinity exceeds that, it leads to influence on some traits of growth and production.…”
Section: Resultssupporting
confidence: 79%
“…Bu nedenle, tuz oranı yüksek olan toprakların değerlendirilmesi ve bitkisel üretim miktarının artırılmasına yönelik çalışmalar gün geçtikçe artmaktadır. Genel olarak bitki büyümesine doğrudan etki eden tuz, bitkinin su alım yeteneğini azaltırken; yapraklarda aşırı birikmesiyle, bitki yapraklarında hasara neden olmakta ve yeni sürgünlerin oluşumunu engellemektedir (Algosaibi et al, 2015). Kinoa bitkisinin diğer tahıl gruplarına oranla daha fazla tuza dayanım göstermesi; bir başka ifadeyle, farklı tuz yoğunluklarına sahip topraklarda yetişebilmesi, araştırıcıların ve üreticilerin dikkatini çekmiştir.…”
Section: T Sunclassified
“…Genel olarak artan tuz yoğunluğuna bağlı olarak bitki boyunda azalma görülürken, yapılan araştırmalardan farklı sonuç elde eden araştırmacılar da olmuştur. Nitekim Algosaibi et al 2015), dört farklı tuz seviyesinde (1.25-4-8-16 dS m -1 ) yetiştirdikleri kinoda, 61 cm'lik en yüksek bitki boyunu 8 dS m -1 tuz yoğunluğunda, 53 ve 54 cm'lik en düşük boy değerlerini ise sırasıyla 4 ve 16 dS m -1 tuz seviyelerinde saptadıklarını bildirmişlerdir.…”
Section: Araştirma Bulgulari Ve Tartişmaunclassified
See 1 more Smart Citation
“…Furthermore, Pereira et al (2020) demonstrated that quinoa varieties represent a good source of bioactive compounds with antibacterial and antifungal activities [17]. The adaption of certain quinoa varieties is possible even under marginal environments where it is notified to be tolerant to many environmental stress conditions including salinity [15,[18][19][20]. Quinoa belongs to a halophyte with over 3000 accessions presenting a large scale of the diversity of salinity tolerance and other traits.…”
Section: Introductionmentioning
confidence: 99%